PEMBERIAN TERAPI OKSIGEN PADA PASIEN ACUTE CORONARY SYNDROME DENGAN CHEST PAIN DI INSTALASI GAWAT DARURAT - Rachmawati, Dewi (LP3M STIKES MUHAMMADIYAH GOMBONG, 2017)
Emergency nurses?s somehow actually routine use of supplemental oxygen theraphy in chest pain patient because of acute coronary syndrome is done, without know that routine oxygen theraphy may potentially cause harm. The used method was by collecting and analyzing related textbook and articles with the use of supplemental oxygen theraphy in chest pain patient because of acute coronary syndrome. The literatures were obtained from textbook and electronic articles such as ScienceDirect, World Health Organization, Google Scholar, PubMed and ClinicalKey with textbook and article criteria that were published from 2000 to 2015. The result is routine use of supplemental oxygen theraphy for Acute Coronary Syndrome (ACS) with chest pain based on physical assessment and level of oxygen saturation. The patient of ACS with chest pain without sign and symtoms hypoxia or respiratory distress, syok and heart failure with oxygen saturation ?94% then without oxygen theraphy, if the patient with one or all of sign and symtoms above with oxygen saturation <94% then oxygen therapy can be given with initial administration is 4 L/minute and in titration until oxygen saturation ?94% with administered more than than 6 hours. The next reassessment is done to the patient. If the condition of the airway patent, the patient can breathe spontaneously, normal breathing (especially rhythm, depth and no respiratory muscle use), respiratory or oxygenation problems minimally and oxygen saturation > 94% then oxygen therapy can be given with nasal cannul 4-6L / minute or simple mask from 6- 10L / minute. If the patient is emergency condition with airway patent, spontaneous breathing with adequate depth ventilation and requiring oxygen in high concentrations may then be provided with a non-rebreathing mask. The conclucion is routine use of supplemental oxygen theraphy in acute coronary syndrom with chest pain not recommended and the oxygen theraphy can be given if the patient with oxygen saturation <94% or sign and symtoms hypoxia or respiratory distress, breathlessness, syok and heart failure Key word :Acute Coronary Syndrome, Chest Pain, Emergency Unit, Oxygen Therapy